Motivation And Job Performances Among Nurses In The Ekiti State Environment Of Nigeria - AWOSUSI; Omojola Omowumi,Ph.D& JEGEDE; Amen Osamede M.Sc (International Journal of Pharma and Bio Sciences, 2011)
This study examined the motivation and job performances among nurses in the Ekiti State environment of Nigeria. Nurses care for individuals, who are healthy and ill, of all ages and cultural backgrounds, and who have physical, emotional, psychological, intellectual, social, and spiritual needs. Data for this study were collected from primary sources. A total number of three hundred (300) questionnaires were administered in this research and the chi-square statistical method of data analysis was adopted in the analysis of the data collected. Results from this study showed that the nurses in the study area were poorly remunerated and motivated, compared to the level of their work performance, working environment, poor working condition of nurses, problems of nurses in the study area affect negatively the level of their job performance in the area. This study therefore recommends that government at all levels should improve the general welfare and remuneration of nurses in the study area. For this will improve the level of job performance of nurses.